2011
DOI: 10.1523/jneurosci.3441-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor α Transforms Astrocytes to a Growth-Supportive Phenotype after Spinal Cord Injury

Abstract: Astrocytes are both detrimental and beneficial for repair and recovery after spinal cord injury (SCI). These dynamic cells are primary contributors to the growth-inhibitory glial scar, yet they are also neuroprotective and can form growth-supportive bridges upon which axons traverse. We have shown that intrathecal administration of transforming growth factor alpha (TGFα) to the contused mouse spinal cord can enhance astrocyte infiltration and axonal growth within the injury site, but the mechanisms of these ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 71 publications
3
64
0
1
Order By: Relevance
“…Interestingly, unipolar or bipolar GFAPexpressing cells (presumed radial glia) have been identified as the principal source of neurogenesis in the adult mouse (Garcia et al, 2004), revealing the proneurogenic effect of directing astrocyte differentiation into these radial glia. Experiments using astrocyte conditioned medium suggested that astrocytes secrete factors that may influence their ability to regain neuronal progenitor potential and dedifferentiate into radial glia (Yang et al, 2009) and TGF-␣ is one factor has been shown to drive astrocyte bipolar morphology in vitro (Zhou et al, 2001;White et al, 2011). EGF is an additional secreted factor that has been implicated in the dedifferentiation of rat astrocytes in culture (Yu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, unipolar or bipolar GFAPexpressing cells (presumed radial glia) have been identified as the principal source of neurogenesis in the adult mouse (Garcia et al, 2004), revealing the proneurogenic effect of directing astrocyte differentiation into these radial glia. Experiments using astrocyte conditioned medium suggested that astrocytes secrete factors that may influence their ability to regain neuronal progenitor potential and dedifferentiate into radial glia (Yang et al, 2009) and TGF-␣ is one factor has been shown to drive astrocyte bipolar morphology in vitro (Zhou et al, 2001;White et al, 2011). EGF is an additional secreted factor that has been implicated in the dedifferentiation of rat astrocytes in culture (Yu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Further study has demonstrated that EGFR induces reactive astrocytes to migrate, undergo hypertrophy, and form a glial scar through activation of the Rheb-mToR signal pathway [50] . Deprivation of EGFR activity in mice results in malformed glial borders and larger lesions after SCi [51] . in addition, EGFR ligands, such as EGF and transforming growth factor-alpha (TGF-alpha), stimulate astrocytes to secrete CSPGs to further form the glial scar [52] .…”
Section: Epidermal Growth Factor Receptor (Egfr) Egfrmentioning
confidence: 99%
“…Various means of reactivating neuron-intrinsic growth programs are emerging, including modulating specific genetic pathways ( Figure 3A and discussed above), providing neuronal cell bodies with specific growth factors (150) or inflammatory factors (51,55,151), or stimulating neuronal activity (152). There is a growing list of chemoattractive growth factors that stimulate and guide regrowth of specific axons after SCI, including BDNF and NT3 for sensory axons (19,88), GDNF for propriospinal axons (89), and IGF1 for corticospinal axons (153), as well as pleotropic growth factors such as FGF and EGF that act in beneficial but undefined ways (154)(155)(156). Modulating axonal cytoskeleton may improve growth cone formation and axon regeneration (38,157,158).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%